POLIGAMI DALAM PERSPEKTIF FAKHR AL-DÎN AL-RÂZÎ DAN FAQIHUDDIN ABDUL KODIR - Rachma Vina Tsurayya (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2019)
One of the religious and social issues that is intriguing and interesting to discuss is polygamy with various differences of opinion in it. This article will compare polygamy in the view of two classical and contemporary scholars, Fakhrudin Ar-Rozi and Faqihuddin Abdul Kodir. The background to the selection of these two figures is due to their opinions in the interpretation of the polygamy verse which is different from most commentators. In this verse we will discuss classical polygamy verse interpretation, verse background, and contemporary polygamy interpretation and then examine the contextualisation in this modern era and can see a more moderate interpretation by comparing them. This study concludes that the problem of polygamy is no longer focused on the underlying motives, but rather on the impact experienced by his wife and children. The interpretation of al-Râzî and Faqihuddin Abdul Kodir has been able to represent the voicing of women's rights in polygamy. This does not get the agreement of all parties, in the sense that there will still be parties that allow it for different reasons. However, the existence of this analysis can help each party to be more sensitive to the reality experienced by women. al-Râzî and Abdul Kodir are on a linear line that has severe conditions for permitting polygamy and encouraging other worship. Although both of them use different approaches and perspectives, they produce thoughts which in the author’s view are almost the same. Keyword: Polygamy; Contextualization; Moderation